Quality of Chicken Sausage Fortified with Nano-Calcium Duck Eggshell in Different Vacuum Packaging during Storage at -18C - Agus Hadi Prayitno; Faradinda Lorenza; Suparmi Suparmi; Muhamad Hafiidh Naafi’yan (Jurnal Ilmu Ternak dan Veteriner, 2021)
This study aimed to determine the effect of fortification of duck eggshellnano-calcium and different types of packaging on the quality of chicken sausage. The sausage was made of duck eggshellnano-calcium, chicken fillet, sugar, garlic powder, salt, pepper, tapioca, ice, oil, soy protein isolate, sodium tripolyphosphate, monosodium glutamate, collagen casing, polyethylene, nylon, and retort pouch packaging. Treatment for fortification of duck eggshellnano-calcium was P0 (0%) and P1 (0.3%) of the total dough. Vacuum packaging treatments were K1 (polyethylene), K2 (nylon), and K3 (retort pouch). All chicken sausages were vacuum-packed and stored at -18°C for 0 and 14 days of observation. Parameters tested were water content, pH value, peroxide value, and total plate count. Data collected were analyzed by analysis of variance in a completely randomized design with factorial patterns and if there was a significant difference (P<0.05) then further tested with Duncan's New Multiple Range Test. Sausage fortified with duck eggshell nano-calcium with vacuum retort pouch packaging was the best treatment with the lowest peroxide value at day 14 shelf life. Sausage fortified with nano-calcium duck eggshell with vacuum retort pouch packaging at day 14 shelf life had moisture (51.59%), pH value (6.83), peroxide value (64.64 meq O2/kg), and total plate count (3.50 X 103 cfu/g).